THE HABITS OF JAMU CONSUMPTION TO KEEP THE BODY HEALTH DURING PREGNANCY AND AFTER CHILDBIRTH IN KAJORAN VILLAGE OF SOUTH KLATEN - Paryono .; Ari Kurniarum (STIKES DUTAGAMA KLATEN, 2013)
Jamu is a traditional herb medicine as one of the efforts that have been widely recognized and utilized by the community with the aim of: treating minor ailments, preventing illness, maintaining resilience and health. Drinking habits herbs commonly found in Javanese society both in the mother during pregnancy, birth and post-birth (parturition).This research is quantitative descriptive study with cross-sectional design, with the sampling techniques by accidental. Data were analyzed by univariate to see the distribution of frequency and descriptive statistics.The results showed the consumption habits of herbs in maintaining a healthy body during pregnancy, after childbirth and while breastfeeding to mothers in Kajoran of South Klaten. By consuming herbs every day there were 33 people (82.5%), every other day there were 6 people (15%) and twice a week there was 1 (2.5%). Some disorder who had experienced during pregnancy such as nausea, vomiting, sore waist, pain, veins and hemorrhoids. Then disorder who had experienced postnatal form of contraction, abdominal pain, pain in the birth canal, fear, anxiety and stomach crimped and disturbance during feeding in the form of reduced milk production, breast pain, breast milk does not come out smooth and swollen breasts. How to use jamu most often of respondents done by drunk found on 35 of the 40 people at the time of breast-feeding and 21 of the 40 people at the time of pregnancy.